A Piece of Hard Light: Excerpts from Michael Crummey’s Hard Light - Steffler, John (Labour/Le Travailleur, 2002)
Abstract In 1998, Newfound land-born writer Michael Crummey published Hard Light, a collection of poems and short prose narratives which explore his ancestors’ experiences in outport Newfoundland and on the Labrador fishery in the 19th and early 20th century. This essay explores the dominant themes in Hard Light, including the experience of work, the power of landscape, and the persistence of culture. It is followed by a selection of Crummey’s poems.